, DALAM KEADAAN (STATUS) IMUNOLOGIS DAN KLINIS PENGOBATAN ANTIRETROVIRAL PENDERITA HIV/AIDS CD38 LIMFOSIT CD8 + , TAMPANG (PROFIL) CD4 + - Ira Puspitawati; Umi S. Intansari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
ABSTRACTThe relationship between immune activation and pathogenesis of Human Immunodeficiency Virus (HIV) infection is unproven. It has been hypothesized that state that HIV-induced activation enhances the magnitude of HIV replication other study shown that viralreplication impaired immune activation. One of the best immune activation marker is CD38 expression on CD8because it has thestrongest significant prognostic markers. It was previously shown that increased CD8+ T-cell activation has predictive value for diseaseprogression but the relation is still controversial. One hypothesis state that HIV-induced activation enhances the magnitude of HIVreplication, other said that viral replication impaired immune activation. To know the profile of immunology and clinical state of HIV/AIDS patients by determining the CD38 molecule expression on CD8+ profiles and clinical state.Crosssectonal, observasional study was done. Twenty nine HIV/AIDS patients who routinely had medical check up and having routine +cells as an activation marker, CD4+antiretroviral therapy at Sardjito hospital and 8 healthy people as normal controls were involved in this study. The count of CD4 +cells counts had significantnegative correlation with WHO stage (p = 0.012). Expression of CD38 molecule on CD8absolute counts and expression of CD38 molecule on CD8 cells were measured using flowcytometry. The CD4+cells of HIV/AIDS patients were highercompared to normal controls, 209.29 ± 76.56, 109.61 + 32.29 respectively (p < 0.05). That expression was not correlated with CD4 + +counts and CD4incrementafter therapy was statistically significant (p = 0.003). The CD4+increment. It might be caused by the time of measurement was not at the begining of diseases. The CD4 + count was negatively correlated with the WHO stage. Expression ofCD38 molecule on CD8+ cells of HIV/AIDS patients were significantly higher compared to normal controls but it wasn’t correlated withthe CD4++ number and CD4+increment after therapy.